Examining gender and sexual orientation differences in physical intimate partner violence experienced and perpetrated by youth living in eThekwini district South Africa during the COVID-19 pandemic - Kalysha Closson; Bongiwe Zulu; Julie Jesson; Janan J. Dietrich; Tatiana Pakhomova; C. Andrew Basham; Mags Beksinska; Angela Kaida (BMC, 2023)
Abstract Background Young women and Lesbian, Gay, Bisexual, Trans, Non-binary/no gender, or Questioning (LGBTQ+) youth in South Africa face some of the highest global levels of intimate partner violence (IPV). Given limited evidence in the wake of the COVID-19 pandemic, which has fuelled IPV globally, we aimed to describe and compare experiences and perpetration of IPV of youth aged 16-24 by sexual orientation and gender identity (SOGI). Methods During the study period (December 2021-May 2022), youth aged 16-24 from eThekwini district, South Africa completed an online survey to understand multilevel impacts of the pandemic on youth. Participants were asked about experiences and perpetration of physical IPV since the start of the COVID-19 pandemic (March 2020). Descriptive statistics and adjusted logistic regressions compared the likelihood of experiencing and/or perpetrating physical IPV between cisgender and transgender inclusive heterosexual men; heterosexual women; gay, bisexual, or questioning men [GBQM]; lesbian, gay, bisexual, or questioning women [LGBQW]; or gender/sexual non-conforming youth [non-conforming]. Results Of 1,588 youth (mean age = 21.7 [SD = 2.3]; 71.7% Black) with non-missing SOGI and physical IPV data, 238 (15.0%) were LGBTQ+ (40.3% LGBQW and 36.1% non-conforming). Overall, 14.6% of respondents experienced physical IPV and 9.8% perpetrated physical IPV since the start of the pandemic, which differed by SOGI (12.3% of heterosexual men, 13.9% of heterosexual women, 22.0% of GBQM, 18.2% of LGBQW, and 25.0% of non-conforming youth experienced and 10.3% of heterosexual men; 7.7% of heterosexual women; 10.0% of GBQM; 18.2% of LGBQW; and 16.7% of non-conforming youth perpetrated). In adjusted models, compared to heterosexual women, non-conforming youth had increased odds of experiencing (adjusted odds ratio [aOR] = 2.36; 95%CI, 1.26-4.39) physical IPV and compared to heterosexual men, non-conforming youth had greater odds of perpetrating physical IPV (aOR = 2.19; 95%CI, 1.07-4.48) during the pandemic. Conclusion Over one in six youth in our study experienced and one in ten perpetrated physical IPV since the onset of the COVID-19 pandemic, with gender and sexual non-conforming youth experiencing and perpetrating IPV at significantly greater rates than cisgender/heterosexual peers. Our findings highlight the need for gender transformative efforts that move beyond the gender binary to support healthy relationships and IPV prevention for LGBTQ + youth in South Africa and globally.